MECHANISM OF MAPPING THE NEED FOR HUMAN RESOURCES DEVELOPMENT IN MICRO INDUSTRY - Siti Arbainah; Jati Handayani; Hadiahti Utami; Kenneth Pinandito (Politeknik Negeri Semarang, 2017)
The common problem often faced by the micro industry is the limited ability of HumanResources (HR). Therefore, HR capabilities need to be improved through appropriatedevelopment programs as needed. This can be achieved if the HR development implementer usesa map of development needs that can be justified as a guideline for implementation. Mapping ofHR development needs can be done in various ways and strategies according to the purpose ofmapping. Appropriate human resource mapping will provide good and useful results, otherwisethe wrong mapping will cause more severe problems. In this article will be presented a mappingmechanism model of HR development needs used in mapping the HR development needs ofmicro-food processing industries in the tourist village of Jambearum, Kendal district. From theresults of interviews and FGD with 13 managers and pemillik of micro-food processingindustries, it can be concluded that the mechanism of problem solving based on hope and realityis the right model for solving micro-industry problems including the problems of human resourcedevelopment. This mechanism model is expected to be included and implemented for similarmicro industries elsewhere.